2006
DOI: 10.1901/jeab.2006.58-05
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Delayed Reinforcement on Variability and Repetition of Response Sequences

Abstract: Four experiments examined the effects of delays to reinforcement on key peck sequences of pigeons maintained under multiple schedules of contingencies that produced variable or repetitive behavior. In Experiments 1, 2, and 4, in the repeat component only the sequence right-right-left-left earned food, and in the vary component four-response sequences different from the previous 10 earned food. Experiments 1 and 2 examined the effects of nonresetting and resetting delays to reinforcement, respectively. In Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 41 publications
(68 reference statements)
6
39
0
6
Order By: Relevance
“…The higher susceptibility of repetitive behaviors to disrupting events replicates findings from previous studies with nonhuman animals (e.g., Abreu-Rodrigues, Hanna, Cruz, Matos, & Dela brida, 2004;Neuringer, 1991;Neuringer et al, 2001;Odum, Ward, Barnes, & Burke, 2006;Wagner & Neuringer, 2006;Ward, Bailey, & Odum, 2006). Nevertheless, one might want to view our results with caution.…”
Section: Disruptive Effectssupporting
confidence: 88%
“…The higher susceptibility of repetitive behaviors to disrupting events replicates findings from previous studies with nonhuman animals (e.g., Abreu-Rodrigues, Hanna, Cruz, Matos, & Dela brida, 2004;Neuringer, 1991;Neuringer et al, 2001;Odum, Ward, Barnes, & Burke, 2006;Wagner & Neuringer, 2006;Ward, Bailey, & Odum, 2006). Nevertheless, one might want to view our results with caution.…”
Section: Disruptive Effectssupporting
confidence: 88%
“…3) observed that variability in the latency to consume grain reward was greater when there was a 3-s interval between an operant response (i.e., the key peck) and the delivery of grain than when grain was delivered immediately after the response. Other studies have demonstrated that pigeons reinforced for performing a stereotyped sequence of pecks become more variable within the sequence when a delay is inserted between the terminal response and reinforcement (e.g., Odum, Ward, Barnes, & Burke, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…As Odum, Ward, Barnes, and Burke (2006) pointed out, under a lag n contingency, the U value is a ''relatively molar measure of variability'' (p. 162), because it is calculated from the frequencies at which each sequence was emitted during an entire session. The percentage of reinforced trials, on the other hand, is a measure affected by ''more molecular aspects of variability'' (p. 162).…”
Section: Local Variability and Molar Variabilitymentioning
confidence: 99%